The 2019 American College of Rheumatology/European League Against Rheumatism Classification Criteria for IgG4‐Related Disease. Issue 1 (2nd December 2019) - Wallace, Zachary S.; Naden, Ray P.; Chari, Suresh; Choi, Hyon; Della‐Torre, Emanuel; Dicaire, Jean‐Francois; Hart, Phil A.; Inoue, Dai; Kawano, Mitsuhiro; Khosroshahi, Arezou; Kubota, Kensuke; Lanzillotta, Marco; et al.
Abstract : Objective: IgG4‐related disease (IgG4‐RD) can cause fibroinflammatory lesions in nearly any organ. Correlation among clinical, serologic, radiologic, and pathologic data is required for diagnosis. This work was undertaken to develop and validate an international set of classification criteria for IgG4‐RD. Methods: An international multispecialty group of 86 physicians was assembled by the American College of Rheumatology (ACR) and the European League Against Rheumatism (EULAR). Investigators used consensus exercises, existing literature, derivation and validation cohorts of 1, 879 subjects (1, 086 cases, 793 mimickers), and multicriterion decision analysis to identify, weight, and test potential classification criteria. Two independent validation cohorts were included. Results: A 3‐step classification process was developed. First, it must be demonstrated that a potential IgG4‐RD case has involvement of at least 1 of 11 possible organs in a manner consistent with IgG4‐RD. Second, exclusion criteria consisting of a total of 32 clinical, serologic, radiologic, and pathologic items must be applied; the presence of any of these criteria eliminates the patient from IgG4‐RD classification. Third, 8 weighted inclusion criteria domains, addressing clinical findings, serologic results, radiology assessments, and pathology interpretations, are applied. In the first validation cohort, a threshold of 20 points had a specificity of 99.2% (95% confidence interval [95% CI] 97.2–99.8%) and a sensitivity of 85.5% (95% CI 81.9–88.5%). In the second, the specificity was 97.8% (95% CI 93.7–99.2%) and the sensitivity was 82.0% (95% CI 77.0–86.1%). The criteria were shown to have robust test characteristics over a wide range of thresholds. Conclusion: ACR/EULAR classification criteria for IgG4‐RD have been developed and validated in a large cohort of patients. These criteria demonstrate excellent test performance and should contribute substantially to future clinical, epidemiologic, and basic science investigations.